Novel hemostatic adhesive powder for nonvariceal upper gastrointestinal bleeding - Park, Jin-Seok (Endosc Int Open, 2019)
Background and study aims  A new hemostatic adhesive powder (UI-EWD) was developed to reduce high rebleeding rates and technical challenges associated with application of currently available hemostatic powders. The aim of the current study was to assess performance of UI-EWD for nonvariceal upper gastrointestinal bleeding (NVUGIB). Patients and methods  A total of 56 consecutive patients that received UI-EWD monotherapy for endoscopic hemostasis due to NVUGIB were retrospectively reviewed. Main study outcomes were success rates with immediate hemostasis and rebleeding within 30 days. Outcomes were analyzed by reviewing patient medical records. Results  Etiologies of bleeding were: post-endoscopic therapy bleeding in 46 (82.1 %), peptic ulcer in 8 (14.3 %), tumor in 1 (1.8 %), and other in 1 (1.8 %). UI-EWD was successfully applied at bleeding site in all cases. The success rate of immediate hemostasis was 96.4 % (54/56), and the 30-day rebleeding rate among patients that achieved immediate hemostasis was 3.7 % (2/54). No adverse event related to use of UI-EWD occurred. Conclusion  UI-EWD was found to have a high immediate hemostasis success rate in NVUGIB when used as monotherapy and showed promising results in terms of preventing rebleeding.